Flexible supercapacitor and method of fabricating the same - Lim, Hong Ngee; Chee, Wei Kit; Ng, Chi Huey; Huang, Nay Ming (2014)
A flexible supercapacitor comprising an electrolyte sandwiched between nickel foams electrodeposited with a nanocomposite. The nanocomposite comprises of a conducting polymer, graphene oxide and a metal oxide. Process of fabricating the flexible supercapacitor is also provided. The process comprises electrodepositing a nanocomposite electro-potentiostatically on a nickel foam from an aqueous solution comprising of a conducting monomer, graphene oxide and a metal salt, placed in one compartment cell followed by compressing an electrolyte between at least two layers of electrodeposited nickel foams.